Trends in HIV, hepatitis B and hepatitis C prevalence among Australian prisoners ‐ 2004, 2007, 2010. Issue 5 (17th February 2014) - Reekie, Joanne M; Levy, Michael H; Richards, Alun H; Wake, Christopher J; Siddall, Deborah A; Beasley, Holly M; Kumar, Shalin; Butler, Tony G
Abstract: Objective: To report the prevalence of markers for HIV infection, hepatitis B and hepatitis C among Australian prison entrants. Design: Cross‐sectional survey conducted over 2‐week periods in 2004, 2007 and 2010. Setting: Reception prisons in New South Wales, Queensland, Tasmania and Western Australia. Participants: Individuals entering prison from the community during the survey periods. Main outcome measure: Prevalence of anti‐HIV antibody (anti‐HIV), hepatitis B surface antigen (HBsAg), anti‐hepatitis B core antibody (anti‐HBc) and anti‐hepatitis C virus antibody (anti‐HCV). Results: The study included 1742 prison entrants: 588 (33.8%) in 2004, 536 (30.8%) in 2007 and 618 (35.5%) in 2010. The age‐standardised prevalence estimates for anti‐HIV, HBsAg and anti‐HBc were 0.4%, 2.3% and 21.7% respectively, and remained stable over the three survey periods. The age‐standardised prevalence estimate for anti‐HCV was 29.0%; it decreased over time (33.3% in 2004 v 23.2% in 2010; P = 0.001), and this coincided with a decrease in prison entrants reporting injecting drug use (58.3% [343/588] in 2004 v 45.3% [280/618] in 2010; P < 0.001). Among injecting drug users, the prevalence of anti‐HCV was 57.2% and did not change significantly over time. Of those who were anti‐HCV positive, 33.7% (140/415) were unaware of their infection status, and 74.3% (185/249) of those who tested positive for anti‐HBc reported that they had never had hepatitis B. Conclusions: HIV prevalence is low in the Australian prisoner population but transmission remains a risk. Despite a decrease in the proportion of prison entrants reporting injecting drug use, prevalence of hepatitis B and hepatitis C has remained high. Treatment and prevention initiatives should be prioritised for this population.